A New Procedure to Estimate Patient-Specific Intraocular Pressure - Redaelli, Elena; Calvo, Begoña; Rodríguez Matas, Jose Félix; Luraghi, Giulia; Grasa, Jorge (Jornada de Jóvenes Investigadores del I3A, 2023)
Measuring Intraocular Pressure (IOP) is a critical field of research in ophthalmology. This work presents and energetic approach to study the Non Contact Tonometry based on the results of a Fluid Structure Interaction simulation. Then, combining these results with clinical images, a new method to estimate the IOP is proposed.